Analysis of axial flux motor performance for traction motor applications. Issue 4 (24th June 2019) - Młot, Adrian; Łukaniszyn, Marian
Abstract : Purpose: Analysis of test data monitored for a number of electric machines from the low volume production line can lead to useful conclusions. The purpose of this paper is to trace the machine performance to find quality-related issues and/or identify assembly process ones. In this paper, the monitoring of experimental data is related to the axial flux motor (AFM) used in hybrid electric vehicle (HEV) and in electric vehicle (EV) traction motors in the global automobile market. Design/methodology/approach: Extensive data analyses raised questions like what could be the causes of possible performance deterioration of the AFM and how many electric motors may not pass requirements during operation tests. In small and medium research units of AFM for HEV or EV, engineers came across a number of serious issues that must be resolved. A number of issues can be eliminated by implementing methods for reducing the number of failing AFMs. For example, improving the motor assembly precision leads to reduction of the machine parameters deterioration. Findings: Assembly tolerances on electric motor characteristics should be investigated during motor design. The presented measurements can be usable and can point out the weakest parts of the motor that can be a reason for the reduced efficiency and/or lifetime of the AFM. Additionally, the paper is addressed to electric motor engineers designing and/or investigating electric AFMs. Originality/value: Performance of AFM was monitored for a number of identical motors from low volume production line. All tested motors were operated continuously for a long period of time and the tests were repeated every few weeks for half a year to check the reliability of motor design and indicate how much the motor parameters may change. The final results point how many motors fail the requirements of motor performance. A few batches of AFM were selected for testing. Each batch represents a different size (nominal power) of the same type of AFM.